Judicial Order in the Examination of the Constitutionality and Legality of Health Financing Norms - Rambe, Muhammad Juang; Siregar, Muhammad Azhali; Sembiring, Danioko (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the role of judicial orders in healthcare financing in Indonesia through decisions by the Constitutional Court (MK) and the Supreme Court (MA). It employs a normative approach with qualitative analysis to explore the role of judicial orders in regulating healthcare financing, focusing on decisions from both MK and MA. The analysis reveals that the MK, through Decision No. 63 of 2012, emphasizes the shared responsibility of the state and individuals in healthcare services, while Decision No. 72 of 2019 upholds the principle of non-regression. The MA, in Decision 7P of 2020, annulled the BPJS premium increase for violating the principle of social justice. This study underscores the importance of legislative responses to judicial decisions to establish a sustainable, fair, and inclusive healthcare financing system aligned with constitutional mandates.